2010
DOI: 10.3802/jgo.2010.21.3.169
|View full text |Cite
|
Sign up to set email alerts
|

GST (GSTM1, GSTT1, and GSTP1) polymorphisms in the genetic susceptibility of Turkish patients to cervical cancer

Abstract: Objective: This work investigates the role of glutathione S-transferase M1 (GSTM1), glutathione S-transferase T1 (GSTT1), and glutathione S-transferase P1 (GSTP1) enzymes and polymorphisms, which are found in phase II detoxification reactions in the development of cervical cancer. Methods: This study was conducted with 46 patients diagnosed with cervical cancer and 52 people with no cancer history. Multiplex PCR methods were used to evaluate the GSTM1 and GSTT1 gene polymorphism. However, the GSTP1 (Ile105Val)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 24 publications
4
28
0
1
Order By: Relevance
“…A study taking into account 150 smoking women diagnosed with cervical neoplasia showed significant association with an increased risk of 4.19-folds of developing cervical cancer in association of GSTM1 null genotypes (40). Other studies confirm that there is a positive association between active or passive smoking, GST null genotypes and the risk of developing cervical cancer (27,28).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…A study taking into account 150 smoking women diagnosed with cervical neoplasia showed significant association with an increased risk of 4.19-folds of developing cervical cancer in association of GSTM1 null genotypes (40). Other studies confirm that there is a positive association between active or passive smoking, GST null genotypes and the risk of developing cervical cancer (27,28).…”
Section: Discussionmentioning
confidence: 61%
“…In the same meta-analysis, smoking is linked between GSTM1 null genotype and cervical cancer (27). In contrast, other studies show that polymorphisms in GSTM1 and GSTT1 genes are not associated with a higher risk for cervical cancer in HPV infected women (16,28). In our study, the GST M1 null genotype was a significant protecting factor for CIS (OR=0.1220, χ 2 =5.25, p=0.0219), while GST T-/M+ genotype was associated with a significantly increased risk for developing LSIL and CIS (OR=7.2592, p=0.0203, and OR=4.6666, p=0.0314, respectively).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…According to the exclusion criteria, 15 articles were excluded including 5 articles containing overlapping population [7][8][9][10][11], 8 precancerous lesions included in the cases [12][13][14][15][16][17][18][19], 2 without sufficient data [20][21]. At last, data were available from 16 individual case-control studies [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37], Table 1 presented characteristics of these 16 case-control studies (a total of 1,627 CC cases and 2,161 controls). 14 studies on GSTM1 polymorphism (a total of 1,514 CC cases and 1,907 controls), 12 studies on GSTT1 polymorphism (a total of 1,187 CC cases and 1,590 controls), and 6 studies on GSTM1-GSTT1 interaction analysis (a total of 791 CC cases and 767controls) were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with Economopoulos et al 's meta-analysis, our meta-analysis had some differences. Firstly, our meta-analysis included three new eligible studies published in Chinese [22][23][24] and two new case-control studies [25][26] in English in 2010, and excluded four studies [13,16,18,19] that had precancerous lesions patients in cases. Secondly, Asians (including Chinese, Indians, Koreans, Japanese and Thais), Caucasians and Latinos were stratified by ethnicity in our meta-analysis, while Chinese (including Koreans, Japanese and Thais) and non-Chinese were stratified GSTM1 AND GSTT1 POLYMORPHISMS AND CERVICAL CANCER RISK Fig.…”
Section: Discussionmentioning
confidence: 99%